plzz answer (I) fast it's urgent
Attachments:
![](https://hi-static.z-dn.net/files/dce/153c5b97c35ace02a9d188f81bca948c.jpg)
Answers
Answered by
0
let. first. zero. is.
Answered by
4
αβ + βY +Yα
(1/2)(1) + (1)(-2) + (-2)(1/2) = -5/2
1/2 -2 -1 = -5/2
1 -4 -2/2 = -5/2
1 -6/2 = -5/2
-5/2 = -5/2
αβY
(1/2)(1)(-2) = -1
(1)(1)(-1) = -1
-1 = -1
please mark it as brilliant answer
(1/2)(1) + (1)(-2) + (-2)(1/2) = -5/2
1/2 -2 -1 = -5/2
1 -4 -2/2 = -5/2
1 -6/2 = -5/2
-5/2 = -5/2
αβY
(1/2)(1)(-2) = -1
(1)(1)(-1) = -1
-1 = -1
please mark it as brilliant answer
Attachments:
![](https://hi-static.z-dn.net/files/dbd/b14b38998d5bdd0021f38afeb6b8e99a.jpg)
Kripa1311:
please mark it as brilliant answer
Similar questions